Strengthening Madrasah Literacy through Change Management Tyagi's Model - Zamroni, Zamroni; Baharun, Hasan; Rohmawati, Eka Fani; Yani, Khalif Oktifan (Lembaga Penelitian dan Pengabdian kepada Masyarakat (Center for Research and Community Services), Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2022)
This study aims to understand the strengthening of madrasa literacy through managing change in the Tyagi model at MTs Negeri 1 Probolinggo. This research uses a qualitative approach with the type of case study, where the researcher uses interviews, observations, and documentation to obtain accurate and valid data. The data analysis uses an interactive analytical model from Miles and Huberman, including data collection, data reduction, data presentation, and concluding. The results showed that the strengthening of madrasa literacy through the management of changes in the Tyagi model at MTs Negeri 1 Probolinggo was carried out through; 1) The power of change, 2) Recognizing and identifying problems, 3) The problem-solving process, 4) Implementation of change, and 5) monitoring, evaluating and measuring change. This research has implications for the importance of literacy culture for madrasas in realizing their vision and mission, so they must be managed in a planned and systematic manner.